2010
DOI: 10.1055/s-0029-1243621
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children and Adolescents Undergoing Surgery for Pectus Excavatum

Abstract: HRQol was significantly better in the Intervention Group compared to healthy controls at the same age. In five subscales Self-Esteem, Behavior, Emotional Role, Mental Health and Family Activities, the PE group had a better HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Long-term follow-up in specific pediatric surgical populations shows that some surgeries are associated with improved HRQOL in the long-term (e.g. pectus surgery, scoliosis surgery) 9,13 , and others are associated with impaired HRQOL (e.g. heart surgery, transplant surgery) 1,8,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow-up in specific pediatric surgical populations shows that some surgeries are associated with improved HRQOL in the long-term (e.g. pectus surgery, scoliosis surgery) 9,13 , and others are associated with impaired HRQOL (e.g. heart surgery, transplant surgery) 1,8,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the first study using a control group found a higher QoL in the intervention group compared to healthy controls in the same age, especially in 5 sub-categories: self-esteem, behavior, emotional role, mental health, and family activities. 5 There was a significant correlation between scores of the children and their parents.…”
Section: Articles Related To Pectus Excavatummentioning
confidence: 91%
“…Since then, interest in patients' quality of life (QoL) has also increased, evident by the studies that have emerged in the last 2 decades. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It is important to bear in mind that QoL is a "concept" which comprises general feelings of satisfaction, well-being (physical and emotional), social belonging, and empowerment. 20 Hence, various questionnaires were developed throughout the years in order to assess QoL in pectus patients, such as the Pectus Excavatum Evaluation Questionnaire (PEEQ).…”
Section: Introductionmentioning
confidence: 99%
“…The scales in the CHQ–CF87 have demonstrated adequate psychometric properties in a number of samples of young people with physical and psychological diagnoses 26 . The CHQ–CF87 is commonly used 2730 , and has been shown to be valid via their significant associations with other important quality of life domains 3135 , as well as their responsivity to treatment 36,37 . Although the CHQ-87 provides a very broad assessment of multiple important domains of physical and psychological function, we determined that one of the scales – Change in Health – was not an appropriate criterion measure in the current analyses, because it assesses perceived change over the past year.…”
Section: Methodsmentioning
confidence: 99%